ASPA code of ethics as a framework for teaching ethics in public affairs and administration: a conceptual content analysis of MPA ethics course syllabi. (3rd April 2021) - King, Stephen M.; Agyapong, Elijah; Roberts, Gary
ABSTRACT: Extant research has demonstrated a positive effect of ethics education in public affairs and administration programs, yet the same suggests the lack of a unifying framework for teaching ethics in the discipline. Since the ratification of the 2013 revised ASPA Code of Ethics, scholars have called for NASPAA programs to incorporate the Code in their curriculum. This article examines the learning objectives and contents of 30 MPA ethics course syllabi. Content analysis was conducted to determine the match between concepts and values in syllabi and the ASPA Code of Ethics. The results indicate that the typical MPA ethics course only partially addresses the full range of ASPA Code of Ethics principles and values. The four most widely shared learning objectives that conform to the ASPA Code of Ethics are a) professional excellence in public service, b) ethical organizations, c) personal integrity, and c) the public interest. Course objectives focusing on constitution and law, democratic participation, social equity, and provision of professional policy advice appear relatively less often. The results are discussed and several suggestions offered to more fully integrate the ASPA Code of Ethics within the typical MPA ethics course curriculum.